The applied value of medical history, physical examination, colour‐Doppler ultrasonography and testis scintigraphy in the differential diagnosis of acute scrotum. (20th February 2018) - Yan, Y.; Chen, S.; Chen, Z.; Pei, X.; Zhou, J.; Xiao, Y.; Wang, X.
Summary: Acute scrotum, especially testicular torsion, is a common surgical emergency. A delay in diagnosis or management may lead to permanent testicular ischaemic damage. Thus, it is particularly important to differentiate testicular torsion from other acute scrotum conditions as soon as possible. Our study has retrospectively investigated 358 patients with acute scrotum admitted to our hospital from the year 2007 to 2016. We have collected a thorough history and clinical data and drew the conclusion by comparing clinical features of different acute scrotum cases, medical history, imaging and surgical findings. Therefore, we propose an innovative "Testicular Torsion (TT) Green Channel" concept. Through the combination of a comprehensive medical history, physical examination and auxiliary colour‐Doppler ultrasonography, the diagnosis of testicular torsion is definite in most circumstances. Testis scintigraphy is a novel and complementary diagnostic modality that can reduce the negative exploration rate in ambiguous and certain cases. The TT Green Channel is a new concept in the management of testicular torsion.